Commemorative Landscape of Dokdo in South Korea – Reflections on Dokdo’s importance in the South Korean national narrative - Hautala, Iina (fi=Turun yliopisto|en=University of Turku|, 2018)
This thesis explores the narrative representations of Dokdo in the memorial sites dedicated to Dokdo and its historical defender An Yongbok. Dokdo is an island located in the waters between the Korean Peninsula and the Japanese Archipelago and a source of an island dispute between South Korea and Japan originating in the Japanese colonial rule over Korea in 1910-1945. By focusing on the Dokdo narratives, this thesis aims to make a small contribution in understanding the meaning of the island for Koreans. This thesis bases on the idea that the narrative representations of the shared past are powerful practices in mediating national histories and identities. The power of narrative is concretized, inter alia, in tangible memorial sites that reveal the logics of narrative representations and affect the process of remembrance. By conducting observations on the memorial sites of Dokdo and An Yongbok, this thesis seeks answers to what is commemorated and how and in what kind of relation to the South Korean national narrative and the memories of the colonial past. By combining observations with a survey research, this thesis also seeks answers to how the museum visitors perceive the museums, especially their importance in teaching about and commemorating Dokdo. The results of the narrative analysis reveal that the Dokdo narrative centers around the feeling of honor and pride toward the South Korean nation, the feeling of regret and acerbity toward Japan, and the feeling of loyalty toward Dokdo. Certain themes appear essential in the narrative. Firstly, Dokdo is interlocked with the Korean history, given an impression of historical continuation and Korea’s solid awareness of Dokdo. Secondly, Dokdo’s protection is represented as a tradition in which masculine heroes have participated throughout the time. Thirdly, Korea’s relation to Dokdo is described in the language of kinship. Fourthly, Dokdo is seen through the island dispute and its background in the colonial past. Finally, the Dokdo narrative is about An Yongbok who appears as a role model for those who protect the South Korean territory. The results of the survey research indicate that the two Dokdo museums succeed in engaging in a conversation with their visitors. According to the survey study, the respondents were satisfied with their museum visit and regarded the museums as important places of commemoration and thought that Dokdo related memorial sites could efficiently change and shape people’s understanding of Dokdo. This thesis reflects that the commemorative landscape of Dokdo is interlocked with the colonial past but lives through the present island dispute. It exists because of the past, in affiliation with the present, waiting for the future. Next, it would be important to study Japan’s point of view in commemorating the island.